Assessment of parasitic fungi for reducing soybean cyst nematode with suppressive soil in soybean fields of northeast China - Jie Song; Shuxian Li; Wei Wei; Yanli Xu; Qin Yao (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2017)
Experiments were conducted to study the inhibitor factors present in suppressive soil that suppressed the soybean cyst nematode (SCN) in the black soil fields with 21 years continuous cropping of soybean (SSSS) and 3 years continuous cropping of soybean followed by 1 year corn (SSSC). Compared with the SSSC field, the densities of SCN significantly (P < 0.05) declined in SSSS field. In a soil microcosm with suppressive soil, the population of SCN decreased after the addition of pimaricin (fungal inhibitor) and streptomycin (bacterial inhibitor), but the population of SCN declined more significantly by adding streptomycin to the suppressive soil than adding pimaricin. Fusarium equiseti, Pochonia chlamydosporia and Purpureocillium lilacinum were isolated from cysts, eggs and J2 of SCN and soil in SSSS and SSC field. The population density of these parasitic fungi was significantly (P < 0.05) higher in SSSS field than in SSSC field. The density of P. chlamydosporia was higher than other fungi. Real-time PCR was used to test genomic DNA of P. chlamydosporia in SSSS and SSC field soil. The mass of genomic DNA and the population density of P. chlamydosporia were significantly (P < 0.05) higher in SSSS field than in SSSC field. This study has revealed that fungi, especially P. chlamydosporia, may play an important role in the suppression of SCN population in the suppressive soil.